High-capacity polyaniline-coated molybdenum oxide composite as an effective catalyst for enhancing the electrochemical performance of the microbial fuel cell - Geetanjali; Rani R.; Kumar S. (My University, 2025)
Microbial fuel cells (MFCs) are a promising technology, which can generate electrical energy by utilizing the organic compound as fuels through central metabolism system of exo-electrogenic bacteria. Anodes have been intensively explored for the development of high-performance MFCs as an alternative to conventional electrodes. Modified anodes were synthesized by the coating of molybdenum oxide (MoO2) and polyaniline (PANI) composites on the carbon cloth (CC) surface. MoO2/PANI electrocatalyst anodes have high capacitance and electrical conductivity, experimentally affirmed by cyclic voltammetry (CV)and charge-discharge analysis. The as-prepared modified anodes were found to efficiently enhance the performance of MFCs by facilitating the extracellular electron transfer from bacteria to the anode. MFCs with MoO2/PANI (1:2 w/w) electrocatalyst anode delivered a maximum power density (PD) of 1101 mW/m2, which was 7.8 times higher than unmodified CC anode. EIS results indicate that the composite MoO2/PANI has also responsible for decreasing the interfacial charge transfer resistance which leads to the improvement in electron transfer between microbes and the modified anode. The results found in the present study will help in the design optimization of novel anode materials to deliver improved PD from MFCs. © 2019 Hydrogen Energy Publications LLC